Hak Notaris Menolak Pembuatan Akta yang Mengandung Unsur Riba dengan Alasan Menjalankan Prinsip Syariat - Prawira, Aditya Yudha; Susilo, Haryanto (Universitas Negeri Malang, 2020)
This study discussed the right of notaries to refuse the creation of deeds containing usuries by reasons of implementing the principles of sharia and the legal implications of notaries based on Article 16 Law on Notary Position. This study was normative research that used conceptual and legislation approaches. Data collection techniques used library studies. The analysis results showed that notaries had the right to refuse the creation of deeds containing usuries based on the theoretical, juridical, and philosophical aspects. Due to the law of notaries that refused the creation of deeds containing usuries, it violates Article Article 16 Law on Notary Position so that notaries could be subject to tieredly administrative action. The Law on Notary Position had not provided legal protection to notaries who practice their profession under the principles of sharia.